Luaran Klinis Maternal pada Pasien Obstetri Dengan Covid – 19 yang Menjalani Seksio Sesarea di RSUP Dr. Sardjito - Hadiwinoto, Bambang; Apsari, Ratih Kumala Fajar; Sudadi, Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Background : COVID-19 is a global pandemic with pregnant women is one of the affected populations. Physiological changes in pregnant women, coupled with the pathological conditions of COVID-19, impact maternal outcomes, including the amount of intrapartum hemorrhage, the requirement for mechanical ventilation, and mortality in patients undergoing cesarean section. Objective : To analyze the impact of OCVID – 19 on the maternal outcomes of obstetric patients undergoing cesarean section at Dr. Sardjito General Hospital. Methods : This research employ a retrospective descriptive study. Secondary data were obtained from medical records of COVID – 19 obstetric patient who underwent a cesarean section at Dr. Sardjito General Hospital from January to December 2021. The data were analyze using descriptive data analysis with SPSS software version 26. Results : The study resulting in a total sample size of 89 patients. The median age of the study subjects was 32 years, with a mean body mass index (BMI) of 28.3 kg/m^2. There was 7% incidence of hemorrhage exceeding 1000 cc , mortality rate was 25,8 %, and 20,2% from the population sample need mechanical ventilation pregnant women undergoing cesarean sections with COVID-19 at Dr. Sardjito General Hospital. Conclusion : There was no significant increase in the incidence of hemorrhage exceeding 1000 cc (7% vs. 18.4%), However there was a noticeable rise in mortality rates (25.8% vs. 0.34%, 1.3%) and an increased need for mechanical ventilation (20.2% vs. 0.071%, 0.01%) when compared to descriptive studies conducted on pregnant women undergoing cesarean sections without COVID-19. Keywords : COVID-19 , clinical outcome, cesarean section